2019 IEEE 28th International Symposium on Industrial Electronics (ISIE) 2019
DOI: 10.1109/isie.2019.8781127
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modality fusion of floor and ambulatory sensors for gait classification

Abstract: In a case study of gait classification from floor and ambulatory sensors, we compare results with data from each modality. The automatic extraction of features is achieved by Principle Component Analysis or Canonical Correlation Analysis, the latter performing better even with a reduced number of components used. Non-linear classifiers are most efficient for fused features. With a Kernel Support Vector Machine around 94% accuracy is demonstrated, improving over the 87% and 79% accuracies obtained with separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Gait events, such as initial contact and toe off, were detected with an accuracy of 100% using IMUs and force sensors installed in shoes in [54]. A kernel SVM was fed features extracted from IMUs and plastic optical fiber-based floor sensors by using PCA and canonical correlation analysis to identify humans with an accuracy of 94% in [31]. Kinetic and kinematic gait features obtained from a 3D motion analysis system and two force plates were fed to linear discriminant analysis and quadratic discriminant analysis classifiers to classify ASD with an accuracy of 82.50% in [22].…”
Section: Related Workmentioning
confidence: 99%
“…Gait events, such as initial contact and toe off, were detected with an accuracy of 100% using IMUs and force sensors installed in shoes in [54]. A kernel SVM was fed features extracted from IMUs and plastic optical fiber-based floor sensors by using PCA and canonical correlation analysis to identify humans with an accuracy of 94% in [31]. Kinetic and kinematic gait features obtained from a 3D motion analysis system and two force plates were fed to linear discriminant analysis and quadratic discriminant analysis classifiers to classify ASD with an accuracy of 82.50% in [22].…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, in this article, the main evaluation metrics will be presented along with their formula, and those who are interested can refer to the relevant paper to get acquainted with other metrics. You need to know this as a recommendation from us that accuracy in this field is introduced either based on the formula [correct/total] [94], [109] or based on [(tp+tn)/(tp+tn+fp+fn)] [156], [157], [158], [159], [160], [161], [162]; this, metric alone, especially with imbalanced data, is not a good measure of classification performance. Therefore, the authors of this article strongly recommend that other metrics are be used to report classification results too.…”
Section: J Evaluationmentioning
confidence: 99%
“…The architecture of the CNN model engineered for this study is shown in figure 2. The model is proposed based on extensive research on gait in our previous work [14], [15], [16], [17]. The model consists of 12 stacked layers to .…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%
“…Therefore, the goal of this work is twofold: firstly, to categorize gait parameters in healthy adults while performing cognitive demanding tasks, using automatic extraction of optimal gait features by deep CNN; secondly, to interpret the model performance on unseen spatiotemporal signals by applying the technique of Layer-Wise Relevance Propagation (LRP) [12] to attempt linking key known events in the gait cycle to cognitive deterioration. As a main data acquisition methodology, the subject's unique gait signatures based on GRF signals were recorded using a set of multiple floor sensors based on plastic optical fiber (POF) technology, in a system specially designed for optimal spatiotemporal sampling [13], [14]. The main sensor fusion and data processing methodology is deep CNNs with LRP applied on the classifications to allow interpretation of the behavioral changes due to a demanding task while walking.…”
Section: Introductionmentioning
confidence: 99%